Telomerase reverse transcriptase promotes chemoresistance by suppressing cisplatin-dependent apoptosis in osteosarcoma cells - Zhengpei Zhang (Nature Portfolio, 2017)
Abstract Cisplatin is one of the most efficacious antimitotic drugs used in the treatment of a range of malignant tumors. However, treatment failures are common due to the development of chemoresistance. In addition to its telomere maintenance function, telomerase plays a pro-survival role, inducing decreased apoptosis and increased resistance against DNA damage. Elucidation of the molecular mechanisms underlying this effect is critical to improve treatment outcomes. Previously, our group showed higher telomerase reverse transcriptase(TERT) expression in cisplatin resistant osteosarcoma cells. In this study, confocal fluorescence microscopy experiments revealed that TERT translocates from the nucleus to mitochondria in cisplatin treated osteosarcoma cells. We observed decreased apoptosis rate and improved mitochondrial function in TERT-overexpressing cells following cisplatin treatment. Based on these results, we further established that TERT inhibits cisplatin-induced apoptosis independently of telomerase reverse transcriptase activity. Moreover, TERT suppressed cisplatin-induced apoptosis and improved mitochondrial function via alleviating intracellular ROS in osteosarcoma cells. Our finding that TERT shuttles from the nucleus to the mitochondrion in response to cisplatin treatment and inhibits cisplatin-induced apoptosis in osteosarcoma cells may be especially important to overcome drug resistance.